2013
DOI: 10.1016/j.celrep.2013.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cyclic AMP Response Element Binding and Hippocampal Plasticity-Related Genes by Peroxisome Proliferator-Activated Receptor α

Abstract: Peroxisome proliferator-activated receptor (PPAR) α is a transcription factor that regulates genes involved in fatty acid catabolism. Here we provide evidence that PPARα is constitutively expressed in nuclei of hippocampal neurons and surprisingly controls calcium influx and the expression of various plasticity-related genes via direct transcriptional regulation of CREB. Accordingly, Ppara-null, but not Pparb-null, mice are deficient in CREB and memory-associated genes, and have decreased spatial learning and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
171
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(188 citation statements)
references
References 44 publications
(35 reference statements)
7
171
0
Order By: Relevance
“…Recently, more and more of WY14643-induced effects on the central nervous system are being reported, such as protective effects against cerebral ischemia/reperfusion (Collino et al 2006), protective effects against oxidative stress-induced cell apoptosis (Collino et al 2006), and inducing neuronal differentiation (Bento-Abreu et al 2007). Roy A et al also found that WY14643 induces the activation of CREB promoter-driven luciferase activity (Roy et al 2013). Here, we supposed that WY14643 may have anti-depressant-like effects.…”
Section: Introductionmentioning
confidence: 81%
“…Recently, more and more of WY14643-induced effects on the central nervous system are being reported, such as protective effects against cerebral ischemia/reperfusion (Collino et al 2006), protective effects against oxidative stress-induced cell apoptosis (Collino et al 2006), and inducing neuronal differentiation (Bento-Abreu et al 2007). Roy A et al also found that WY14643 induces the activation of CREB promoter-driven luciferase activity (Roy et al 2013). Here, we supposed that WY14643 may have anti-depressant-like effects.…”
Section: Introductionmentioning
confidence: 81%
“…Although the hippocampus does not metabolize fat, recently we have demonstrated that PPARα is constitutively expressed in the hippocampus and hippocampal neurons (11). Here, we describe that activation of PPARα induces the expression of ADAM10 and subsequent α-secretase proteolysis of APP.…”
mentioning
confidence: 82%
“…The consensus sequence of the PPRE is AGGTCAAAGGTCA, which consists of a direct repeat of AGGTCA half-sites with one base-pair spacing (DR1) (Kliewer et al, 1992;Wahli and Michalik, 2012). However, imperfect half-sites of the canonical DR1 have been identified in PPARaregulated genes, such as CYP4A1 (AGGGTAAAGTTCA), very low density lipoprotein receptor (AGGTCAGATGGCA), cyclic AMP response element binding (AGGTCAAAGGACA), the mouse hypoxia-inducible lipid droplet associated (AGGG GAAAGGTCA), and the rat ACOX (AGGACAAAGGTCA) (Juge-Aubry et al, 1997;Roy et al, 2013;Gao et al, 2014;Mattijssen et al, 2014). It is widely accepted that the sequence of the 59-flanking region (6-or 7-bp segment) in addition to the consensus DR1 sequence is important for binding of PPAR to various PPREs (Palmer et al, 1995;Juge-Aubry et al, 1997;Chandra et al, 2013).…”
Section: Cyp2c8 Is a Novel Target Of Ppara In Human Livermentioning
confidence: 99%